Inquiry into poverty and financial hardship - FaHCSIA (My University, 2003)
In October 2002 the Australian Senate referred, for inquiry and report, questions related to poverty and financial hardship to the Senate Community Affairs References Committee. The former Department of Family and Community Services responded to the Committee's request for submissions as part of their information gathering process. This Occasional Paper reproduces the Department's submission. The key themes of the submission are: •Australia has high and rising living standards with the benefits having been shared widely across the community. •While some Australians continue to face disadvantage this is often the result of a number of compounding factors and the existence of multiple disadvantage. •Traditional approaches to poverty which tend to focus on the use of simple income measures are not adequate to identify this type of problem, nor do they provide guidance on the factors which cause it. •The important challenges for social policy, in addition to tackling this form of multiple disadvantage, concern improving economic participation where this is possible. •This focus is underpinned by the need to respond to the changing demographic landscape of Australia, with recognition that economic participation is important not just for the welfare of families and individuals while they are of working age, but in promoting greater levels of well-being in retirement.
Keywords: Stress -- Life events; Disadvantage; Disadvantage, adversity and resilience; Disadvantage; Stress; Life events; Adversity and resilience; Dsiadvantage, adversity and resilience